Renal injury in the setting of immune checkpoint inhibitor: Report of a case of hypothyroidism and the role of positron emission tomography. Issue 3 (October 2020) - Heybeli, Cihan; Nathan, Mark A; Herrmann, Sandra M
The use of immune checkpoint inhibitors has been increasing rapidly. Numerous untoward immune-related adverse events due to immune checkpoint inhibitors have been reported. Acute interstitial nephritis due to immune checkpoint inhibitors is one of these immune-related adverse events. Although gold standard, it is not always straightforward to perform a kidney biopsy in oncological patients. Helpful diagnostic methods are lacking. In this case report, we discuss the potential role of positron emission tomography–computed tomography on supporting the diagnosis of acute interstitial nephritis or ruling it out in the setting of acute kidney injury following treatment with immune checkpoint inhibitors. Studies are needed to assess the possible role of positron emission tomography–computed tomography for the diagnosis of acute interstitial nephritis in these subjects.